PENERAPAN METODE FLASH CARD TERHADAP KEMAMPUAN KOGNITIF ANAK AUTIS DI RA SUNAN GIRI TAJINAN-MALANG - Ernawati; Sholichah, Norma Ita (JURALIANSI: Jurnal Lingkup Anak Usia Dini, 2023)
Education for autistic children can be properly considered in terms of providing facilities and infrastructure that support developmental aspects like normal children. The aim is to describe cognitive abilities in early childhood. The research method used is qualitative in this type of descriptive research. Data collection techniques used observation, interviews and documentation on four children at RA Sunan Giri Tajinan-Malang in 2021 data. The results and discussion of the cognitive development of children with autism can be seen from the form of understanding of concepts and visual abilities in children. These changes occur during the growth and development period since pre-prenatal. So, educators carry out treatment as a simple therapy in learning flash cards in the cognitive field. The diversity of media in the form of colored flash cards is able to provide stimulus to children's cognition more effectively and efficiently. Apart from that, flash card media helps train children's physical motor skills such as mouth movements. As well as, assisting in forming an understanding of the material in thinking patterns through face to face, group and individual techniques using conceptual methods as a learning strategy. The researcher's suggestion is to create an attractive and modern form of flash card media.